2011
DOI: 10.1159/000329700
|View full text |Cite
|
Sign up to set email alerts
|

Higher Executive Control and Visual Memory Performance Predict Treatment Completion in Borderline Personality Disorder

Abstract: Background: Non-completion of a prescribed course of treatment occurs in 20–60% of individuals diagnosed with borderline personality disorder (BPD). While symptom severity, personality traits and environmental factors have been implicated as predictors of treatment non-completion (TNC), there have been no studies of neuropsychological predictors in this population. Methods: From a randomized controlled trial, a subsample of 31, unmedicated outpatients diagnosed with BPD with recent self-injurious behavior was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…A systematic review of treatment attrition in BPD patients undergoing psychotherapy [35] highlighted factors such as poor therapeutic alliance, low motivation to change and high impulsivity as predictors of therapy attrition. Recent neuropsychological research has also demonstrated that lower executive control and visual memory performance predict dropout [37]. Measures of such factors could be used for improving completion rates in DBT as well as in other psychotherapies which have been demonstrated to improve outcomes in the BPD population, such as transference-focused therapy [38], schema-focused therapy [39], STEPPS [40], mentalisation-based therapy [41], and narrative exposure therapy [42].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of treatment attrition in BPD patients undergoing psychotherapy [35] highlighted factors such as poor therapeutic alliance, low motivation to change and high impulsivity as predictors of therapy attrition. Recent neuropsychological research has also demonstrated that lower executive control and visual memory performance predict dropout [37]. Measures of such factors could be used for improving completion rates in DBT as well as in other psychotherapies which have been demonstrated to improve outcomes in the BPD population, such as transference-focused therapy [38], schema-focused therapy [39], STEPPS [40], mentalisation-based therapy [41], and narrative exposure therapy [42].…”
Section: Discussionmentioning
confidence: 99%
“…Also, predictors of psychotherapy success could be depicted. Fertuck et al [155], for example, found that better baseline visual memory performance as well as better executive functioning predicted short durations of treatment in dialectical behavior therapy, supportive therapy, or drug treatment. These studies already point to the fact that the feasibility of the proposed studies is a difficult issue, as even in these studies treatments were intermixed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that strategies to improve protocol adherence and participant retention may include enrolling people at early disease stages such as in amyotrophic lateral sclerosis clinical trials [10]. In line with this hypothesis, higher executive control and visual memory performance was shown to be associated with treatment completion in borderline personality disorder clinical trials [11]. On the other hand, restricting eligibility criteria may have implications on recruitment rate, which both add to the duration and cost of the trial.…”
Section: Discussionmentioning
confidence: 88%